Formação de professores e tecnologias: uma discussão sobre semelhança de triângulos - Sant'Anna, Viviane Nogueira Ponciano (2020)
This research focuses on the training of basic education teachers in contexts mediated by digital technologies. From a mathematical theme, the similarity of triangles, didactic and historical contributions are constituted, which, in turn, gave rise to studies related to the notions of congruence, proportionality, parallelism, geometric transformations, among others. These studies, together with the theoretical contributions related to teacher training in scenarios with the presence of digital technologies, gave rise to a series of activities, based on the central objective of the proposal, which is to reflect on what contributions to the resignification of knowledge about the similarity of flat figures (and triangles in particular) can come from the construction of didactic strategies with the use of digital technologies in a proposal linked to the formation of teachers and their practice. The methodological approach brings elements of Didactic Engineering and the activities are analyzed taking into account the levels of figural apprehension that may arise from the conjectures eventually made by the apprentices, the questions related to mathematical knowledge and its intrinsic connection, in this case, to fluency and perception about the interactive potential of the technological interface involved. As a result, from the context of the activities we bring a discussion of didactic questions related to the exploration of suggested constructions, carried out through the GeoGebra software